2014
DOI: 10.1590/0103-6440201302434
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response and Time-Course of a-Tocoferol Mediating the Cytoprotection Of Dental Pulp Cells Against Hydrogen Peroxide

Abstract: This in vitro study evaluated the potential protective effect of vitamin E alpha-tocopherol (α-T) isomer against the toxicity of hydrogen peroxide (HP) applied on dental pulp cells. Odontoblast-like MDPC-23 cells were seeded on 96-well plates for 72 h, treated with different concentrations of α-T (1, 3, 5, and 10 mM) for different times (1, 4, 8, and 24 h) and then exposed or not to a 0.018% HP solution for 30 min. In positive and negative control groups, cells were exposed to HP or culture medium (DMEM contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Prebleaching administration of anti-inflammatory drugs and topical application of sodium fluoride and potassium nitrate desensitizing agents as well as the use of antioxidant molecules have been widely assessed. 8 9 10 11 12 13 14 15 Since the pathway for pulp tissue damage following tooth bleaching involves oxidative damage to pulp cells, therapies using antioxidant agents have been recognized as interesting alternatives for preventing the occurrence of conditions leading to intense oxidative stress. 13 15 Antioxidant agents have been successfully used to restore optimal bonding after bleaching treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prebleaching administration of anti-inflammatory drugs and topical application of sodium fluoride and potassium nitrate desensitizing agents as well as the use of antioxidant molecules have been widely assessed. 8 9 10 11 12 13 14 15 Since the pathway for pulp tissue damage following tooth bleaching involves oxidative damage to pulp cells, therapies using antioxidant agents have been recognized as interesting alternatives for preventing the occurrence of conditions leading to intense oxidative stress. 13 15 Antioxidant agents have been successfully used to restore optimal bonding after bleaching treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 10 11 12 13 14 15 Since the pathway for pulp tissue damage following tooth bleaching involves oxidative damage to pulp cells, therapies using antioxidant agents have been recognized as interesting alternatives for preventing the occurrence of conditions leading to intense oxidative stress. 13 15 Antioxidant agents have been successfully used to restore optimal bonding after bleaching treatment. 16 17 18 In addition, previous studies have demonstrated that antioxidant molecules, such as alpha-tocoferol and ascorbic acid (AA), were capable of preventing HP-mediated pulp cell damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 16 studies were excluded, and the reasons for their exclusion can be found in Figure 1 and Supplementary Data 1 [ 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. Twenty-seven studies meeting the inclusion criteria were selected for qualitative analysis [ 1 3 6 11 12 17 23 24 25 26 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…9,10 The anti-inflammatory substances and low level laser therapy used have been tested and can promote reduction of pulp damage after dental bleaching, but the results are not conclusive. 9,14 The reduction of the bleaching gel concentration used in in-office bleaching is also an option to minimize the damage. 7,8,31 However, this product requires repeated sessions containing lower H 2 O 2 concentration, 6 a procedure which may also increase the damage to pulp tissue.…”
Section: ;28:e20190384 7/10mentioning
confidence: 99%